Preliminary Psychometric Analysis of a School as a Learning Organization Scale in Special Education Settings - Andita Putri Ramadhania; Mohammad Sofwan Effendi; Kamaludin Kamaludin (Green Publisher Indonesia, 2026)
Schools are increasingly conceptualized as learning organizations; however, psychometrically sound instruments for assessing this construct in special education contexts remain limited. This study aimed to examine preliminary Rasch-based psychometric evidence for an adapted School as a Learning Organization (SLO) scale administered to teachers in special education settings. The instrument comprised 76 items representing seven theoretically defined SLO dimensions. Data were collected from 40 teachers working in public special schools in Indonesia. Content validity was examined using expert judgment procedures involving six experts in special education, educational psychology, psychometrics, and organizational development. Item-level and scale-level Content Validity Index (CVI) values met recommended criteria, indicating satisfactory content relevance and clarity. Responses were recorded using a four-point Likert scale to reduce neutral response tendencies. Rasch measurement modeling was applied separately to each dimension to evaluate item fit, person and item reliability, and measurement precision. Most items demonstrated acceptable fit to the Rasch model. Item reliability indices were generally high, indicating stable item difficulty ordering, while person reliability varied across dimensions, reflecting differences in respondent differentiation. Pearson correlations among dimensions were positive and moderate to strong, supporting the theoretical coherence of the SLO construct. Given the modest sample size, findings are interpreted as preliminary. Nevertheless, the results provide early measurement evidence supporting the use of the adapted SLO scale in special education contexts and offer a foundation for further validation using larger and more diverse samples.